Pembuatan Sistem Informasi dengan Analisis dan Perancangan Berorientasi Objek - Pelawi, Dewan (Bina Nusantara University, 2013)
To generate an information system which is in accordance with the needs of company requires an analysis of business processes by observing the running system. Solutions for problems found when doing the business are observed using the systems approach. Object-oriented analysis and design is a method currently used to build an information system. The system development with